Penerapan Teknologi Media Tanam Hidroponik untuk Mewujudkan Wisata Pertanian di Desa Cimekar - Parsono, Slamet; Zakiyuddin, Ahmad; Utami, Indri (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2021)
Agricultural-based tourism villages are a great opportunity for rural communities to explore the potential of their area. Through hydroponic plant processors on limited land it provides a special attraction for visitors / tourists. This article reviews how the socialization and outreach activities of hydroponic planting media to residents of RW 28 Cimekar Village, Cileunyi District, Bandung Regency. The goal is to generate a climate for agricultural tourism in Cimekar Village and increase employment and income for the surrounding community. The method used is one of them by directly visiting the community which is concentrated in several places to conduct counseling. Socialization activities are carried out by conducting direct simulations on how hydroponic plant technology is able to develop in limited land. The result is that the community feels how the transfer of technology for this hydroponic growing media can be easily practiced.